Fluidic-Based Instruments for Space Biology Research in CubeSats - Harandi, Bijan; Ng, Simon; Liddell, Lauren C.; Gentry, Diana M.; Santa Maria, Sergio R. (Frontiers in Space Technologies, 2022)
For the last 15 years, small satellites known as CubeSats have been used to investigate the effects of the space environment on biological organisms. All biological CubeSat missions flown to date have performed studies in low Earth orbit (LEO), each one improving its biological support sub-systems from the last. An upcoming NASA biological CubeSat mission, BioSentinel, will launch as a secondary payload on Artemis 1 and eventually reach a heliocentric orbit beyond LEO, and the protection of Earth's magnetosphere. The main objectives of BioSentinel are (1) to investigate the biological effects of the deep space radiation environment and (2) to develop our technological capacity to support biological research in deep space. The instruments and subsystems within BioSentinel have heritage from previous CubeSat missions (e.g., fluidics, optics, thermal control), but are extended on many levels. BioSentinel improves upon the materials and design (e.g., decreased card vapor permeability to maintain low humidity; the addition of a fluidic manifold with internal check-valves, desiccant chambers, and bubble traps for each individual fluidic card) and adds new tools for discovery (e.g., onboard LET spectrometer). The main objective of this Perspective is to emphasize the evolution of the fluidic systems used in past and ongoing NASA biological CubeSat missions and highlight aspects of these systems that can be optimized for future experimentation beyond LEO.